Where the rubber of the RISP model meets the road: Contextualizing risk information seeking and processing with an avalanche bulletin user typology. (December 2021) - Clair, Anne St.; Finn, Henry; Haegeli, Pascal
Abstract: In risk communication research, the Risk Information Seeking and Processing (RISP) model has established itself as a valuable tool for explaining differences in how people reason with risk information. However, the generic nature of its dependent variables, information seeking (routine or nonroutine) and processing (heuristic or systematic), seems to limit its capacity to produce tangible directives for improving risk communication product design. Studying avalanche risk communication provides an opportunity to conduct empirical research to better understand how information seeking and processing behaviors explicitly manifest themselves in a specific context and with respect to a particular product. The primary tool that avalanche warning services use to inform winter backcountry recreationists about avalanche hazard is the public avalanche bulletin, which summarizes conditions for a mountain region over a given time. Addressing an industry need to evaluate avalanche bulletin effectiveness for the range of backcountry recreationists in Canada, we conducted 46 semi-structured interviews with an inclusive sample to shed light onto how recreationists incorporate bulletin information into backcountry travel decisions. We combined applied thematic analysis with correspondence analysis to detect and classify patterns in recreationists' bulletin use into an Avalanche Bulletin User Typology that explicitly describes users' information seeking and processing behaviors. The identified patterns reveal a distinct hierarchy in the complexity of information reasoning, which parallels the Structure of Observed Learning Outcomes (SOLO) taxonomy, a well-established education theory. The results illustrate new opportunities for designing risk communication products with evidence-based and context-specific guidance to reach and resonate with audiences more effectively.